Design Challenges and Possible Solutions for 5G SIW MIMO and Phased Array Antennas: A Review - Sayyed Arif Ali; Mohammad Wajid; Ajay Kumar; Muhammad Shah Alam (IEEE Access)
With the increasing demand for high-speed data, rapid deployments of the 5G terrestrial heterogeneous wireless networks are expected worldwide in the next decade. In such networks, sub-6 GHz macro-cells overlapped by mmWave small-cells are being used to cater to densely populated regions.As a result, several challenges arise with the antenna design technologies used at the mobile terminal, access points, or backhaul/front haul levels. These challenges are being addressed using multiple-input multiple-output (MIMO), massive-MIMO, and phased array antenna technologies. In order to implement these antenna technologies, considering the expanding 5G scenario, substrate integrated waveguide (SIW) offers a viable solution due to its low-cost, low-profile, high-power handling, low transmission loss, and ease of integration with the radio circuits; therefore, the SIW plays a vital role in developing the modern radio systems. The proposed study aimed to provide a comprehensive overview of SIW MIMO and phased array antennas operating in the 5G sub-6 GHz and mmWave bands. It deliberates the specific issues related to the band of operations and challenges in designing different antenna structures. After careful investigation and detailed analysis, this paper identified existing research gaps and suggested possible antenna design solutions for prospective researchers who intend to explore further the aforementioned promising area and present future research directions.